Walking into Clarity: The Dynamics of Self and Place in the Poetry of Ivor Gurney. Issue 2 (2nd July 2016) - Rawling, Eleanor
Abstract : In the first issue of this journal, Eric Magrane called for a renewed concern with "geopoetic texts and practices that draw on the work of poets as well as geographers." This article focuses on the English poet, Ivor Gurney, as a means of exploring the relationship between the act of walking and the process of poetic writing. Despite periods of mental instability and the traumatic experience of serving as an ordinary soldier in World War I, Gurney reveals, through his poetry, his intense passion for and close entanglement with his native Gloucestershire places. I examine some of Gurney's poetry and draw on recent developments in cultural geography to suggest that what Gurney describes as "walking into clarity" might be seen as a continual dialogue and negotiation taking place between the poet and his places. Gurney's creativity, however, arises from more than just the immediacy of the walking moment. I argue that Gurney's poetry reveals a performative engagement with a known and loved locality—the knowing and observing eye being as important as the affective encounters in his creative practice. Attunement to the local provides him with the foundation from which his walking footsteps weave a new dynamic of self and place.